By characterizing metabolic and immune microenvironment reveal potential prognostic markers in the development of colorectal cancer - Liangliang Liao; Yongjian Gao; Jie Su; Ye Feng (Frontiers in Bioengineering and Biotechnology, 2022)
Colon adenocarcinoma (COAD) is one of the deadliest cancers in the world and survival rates vary significantly between early and advanced stage patients. Therefore, the identification of the pathogenesis in the development of COAD and prognostic markers is urgently demanded. Herein, we collected RNA-seq and somatic mutation data of COAD for statistical analysis. Clinical stage-specific differentially expressed genes (DEGs) and tumor development-dependent DEGs were identified. By characterizing the metabolic and immune features of COAD between stages, we found that the energy supply and inflammatory response of advanced tumors were suppressed. Next, the ETS1, AR, GATA1, GATA2, SREBF1, FOXP3, STAT4, and NFKB1 were identified to drive the metabolic and immune-related pathways in the development of COAD. The three potential prognostic markers (HOXC8, IRF7, and CXCL13) were identified based on Cox regression analysis. Additionally, immune infiltration analysis revealed that the resting CD4+ T cell was significantly related to the overall survival (OS) of COAD patients. Collectively, the specific metabolic and immune characteristics of advanced patients and the identified prognostic biomarkers will contribute to the development of precision medicine.